A CLINICAL CASE OF CORTICAL DEAFNESS IN A PATIENT WITH SYMMETRICAL CYSTIC TRANSFORMATION OF CEREBRAL HEMISPHERES - G. A. Karkashadze; L. V. Toropchina; A. V. Anikin; A. K. Gevorkyan; M. Z. Karkashadze; G. V. Kuznetsova (Педиатрическая фармакология, 2014)
Cortical deafness is a complete absence of the function providing a person with an ability to perceive audible signal caused by defects of cortical centers of hearing of both cerebral hemispheres. This rare pathology is caused by peculiarities of bilateral organization of hearing in cerebral cortex. The article presents a case of diagnosing cortical deafness confirmed with data of a clinical trial and magnetic resonance imaging (MRI) of the brain. It ought to be observed that accurate diagnosis was provided by prescription of the child’s brain MRI despite the absence of specific indications for such an examination.